CO, PO, CLO, PLO, CO-PO Mapping and Bloom’s Taxonomy of the Climatology and Biogeography with Course Code: Geo-C-502 of Postgraduate Sikkim University - aTanka Prasad Dhungel, bChandra Prasad Khatiwada (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
The continuous improvement of teaching-learning processes in higher education relies on clearly defined outcomes and structured assessment mechanisms. Present research is the first report to presenting the Course Outcomes (CO), Course Learning Outcomes (CLO), Program Outcomes (PO), and Program Learning Outcomes (PLO) are crucial components in outcome-based education (OBE) of the Climatology and Biogeography with Course Code: Geo-C-502 of Postgraduate subject of Sikkim University. Bloom’s Taxonomy provides a hierarchical classification of cognitive skills essential for formulating effective learning objectives. CO-PO Mapping establishes the correlation between what is taught (COs) and the overarching goals of a program (POs). This paper discovers the interrelationship between these elements, emphasizing the importance of systematic curriculum design and assessment of Climatology and Biogeography.